Sistem Informasi Akademik SMKN 6 Muaro Jambi - Yuli Yani Lubis, Dina; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2022)
The development of information technology, especially the use of the system allows the data processing become more efficient, faster and accurate than the system that is still done manually. One is the Academic Information System is used to provide ease of data processing. With a design that takes into account the facility and understanding of the human resources that will use this information system is expected to run well if it will be implemented. This study proposes an analysis and design of a prototype of a system of academic information in SMKN 6 Muaro which provides convenience in data processing and obtain information.